(untitled) (REMUNOM, 2024)
The safrinha corn crop plays a fundamental role in agriculture, contributing significantly to the national economy, this crop requires a large amount of nutrients for its good development. Among the various nutrients necessary for the good development of this crop, nitrogen stands out, a fundamental and indispensable element in crop fertilization, playing a strong role in maintaining and increasing productivity. Nitrogen stands out from other nutrients because it presents a marked dynamism in the soil system and because it is normally the nutrient required in greatest quantities by crops. There are several sources of this element, urea being one of the most important due to its low cost and high concentration of N. However, it is important to consider the various transformations that nitrogen undergoes in the soil, whether organic or mineral, which can be mineralized, immobilized, nitrified or denitrified, in addition to losses that may occur due to volatilization and leaching. In view of the above, a review was carried out in which we sought to identify the main factors that may interfere with the use of nitrogen in the soil for the cultivation of off-season corn. It was found that the sources and form of application can directly influence the dynamism of nitrogen in the soil and plant relationship, which can increase availability and increase efficiency, thus ensuring greater profitability and preservation of the environment. Keywords: nitrogen, off-season corn, slow release sources, nitrification inhibitors.